Massage Therapy For Breast Cancer Complaint - Susan Susyanti; Aneng Y; Rachmat Ch (STIKes Karsa Husada Garut, 2015)
Breast cancer is one of the leading causes of cancer death, usually affects women aged 18- 54 years, especially high risk in women aged 45 years, amounting to 25% (Lee, 2008). Based on the results of research on breast cancer, there were 26 cases per 100,000 women with breast cancer each year. The existence of the phenomenon certainly brings concern for all of us to the risk of increasing the incidence of breast cancer. During the various treatments performed on patients with breast cancer, such as surgery, chemotherapy, radiation, and hormone therapy. Therapy is not always profitable and successful, but can cause side effects. Recent research suggests non-pharmacological treatment such as self-hypnosis, relaxation, massage and acupressure therapy proven to reduce the side effects of chemotherapy. Massage therapy as an alternative treatment proven to reduce a variety of physical complaints / psychological result of chemotherapy. Various journals have published the results of research on the positive effects of massage therapy in relieving many complaints in patients with breast cancer due to chemotherapy and radiation therapy. Data collected in the form of literary journals that published research results, traced using CINAHL-EBSCOhost, ProQuest, PubMed, HealthMed Journal, with the key word